Facebook Ads, COVID-19, and Smart City Dissemination - Agus Dwianto, Rahmad; Bakhtiar Darmawan, Arief; Priyo Purnomo, Eko; Fathani, Aqil; Salsabila, Lubna (KnE Social Sciences, 2023)
This research provides an innovative strategy to disseminate smart city programs during the pandemic through Facebook Ads. Socialization of the smart city program was hampered due to the COVID-19 pandemic. The study used the systematic literature review method from various recent journals on the use of Facebook for the dissemination of public policy information. NVivo tools, qualitatively in-depth and comprehensive analysis will explain new methods’ findings in this digital age. Facebook ads were chosen because the field can target those who have an interest in smart cities. This study found that Facebook advertising as a digital platform for socializing smart city programs during the pandemic the public was more efficient in terms of time, effort, cost, and a wider target market. This study found an innovation, namely the use of Facebook advertising as a digital marketing platform in government affairs or the socialization of government programs to the public during the pandemic. Further studies could combine Facebook Ads with other platforms like Google Ads, SEO, and TikTok. Keywords: COVID-19 Pandemic, Digital Platform, Smart City